Wear monitoring based on the analysis of lubricant contamination by optical ferroanalyzer - Myshkin, NK; Markova, LV; Semenyuk, MS; Kong, H; Han, HG; Yoon, ES (ELSEVIER SCIENCE SA, 2003)
Lubricant contamination analysis is one of the common and prospective methods of machine condition monitoring. Wear debris formed in rubbing is a source of valuable information on the wear mechanism and severity, while total oil contamination gives information on oil lubricity. Development of new methods and means of reliable condition monitoring of friction units remains a challenging task for rating the condition of equipment, reducing losses for idle time or failures, and saving lubricants. Despite the fact that direct reading (DR) ferrograph was proposed more than 20 years ago its main principle-accumulation and estimation of deposited particles content-underlies the basis of creation of new effective built-in devices and criteria for condition monitoring. In the presented paper, the principle of operation of the optical ferroanalyzer (OF) jointly developed by V.A. Belyi Metal-Polymer Research Institute of Belarus National Academy of Sciences and Korea Institute of Science and Technology is presented. Optical ferroanalyzer in addition to ferrograph allows us to estimate total contamination of oil, increasing reliability of tribosystem condition monitoring. The results of bench tests of the analyzer are described and example of its application for condition monitoring of engine is shown. (C) 2003 Published by Elsevier Science B.V.